La madera como alternativa constructiva y sustentable en viviendas unifamiliares en la ciudad de Bogotá (2024)
In Bogotá, earthquake-resistant construction is crucial due to geographical conditions. Considering the seismic vulnerability of homes in the city, wood emerges as an alternative structural material due to its inherent properties. However, its usage is límited. To demonstrate the potential of wood as an efficient, economical, and sustainable material, three alternatives for wood construction systems were proposed, comparing modular construction, post and beam, and wood FACULTAD DE INGENIERÍA AMBIENTAL Y CIVIL framing. The primary focus of the evaluation was on construction time and costs. Additionally, the advantages, disadvantages, and raw material requirements of each system were assessed to ensure compatibility with the NSR-10 regulations.